Bi-objective economic feasibility of hybrid micro-grid systems with multiple fuel options for islanded areas in Egypt - Abo-Elyousr, Farag K.; Elnozahy, Ahmed (Renewable energy, 2018)
The main target of this research is to allow modern distributed energy resources (DERs) to contribute effectively in the economic feasibility of hybrid renewable power generation system. There are several factors such as the net present cost (NPC), levelized cost of energy (COE), amount of greenhouse gases (GHG) emissions, and the ability of the hybrid system to meet the load at different meteorological conditions to consider when evaluating the effectiveness of hybrid generation system within microgrids. A multi-objective based optimization algorithm to reduce cost, emissions, and a combined solution between cost and emissions is investigated in this research. This research presents an approach to optimize a hybrid microgrid (HMG) system with different fuel options. The power management approach determines the optimal sizing of DERs based on ant colony optimization (ACO) algorithm. In order to find the best configuration, the obtained results are compared with genetic algorithm (GA), particle swarm optimization (PSO), and HOMER. Three isolated areas in Egypt with different metrological conditions are selected for optimization of HMG system, namely: Kharga, Saint Katherine, and Qussair. The results show that the combined optimal configuration of HMG system is better in satisfying load demands without violating any restraints. •Optimal configuration and sizing of hybrid microgrid systems.•A bi-objective problem is proposed to decide the optimal yearly renewable and DERs outputs.•The developed method is effective to offer an optimal configuration for all investigated areas.•PV generator and natural gas turbine are superior to biomass generator in reducing COE objective.•Developed BOACA algorithm offers optimal HMG system configuration and sizing.